Development of Educational Pocket Comics (Komikusi) as Learning Media to Improve Reading Comprehension Skills of Class IV b Students of SDN Harjosari Lor 03 - Fitria Salsabila Khoirunisa; Sukardi Sukardi (Universitas Muhammadiyah Malang, 2025)
Understanding the content of a reading is an important aspect of reading activities. Understanding the content means the reader has successfully received information from the reading. However, in reality, many people have difficulty understanding the content of the reading, which was also found by researchers when conducting pre-research activities at SDN Harjosari Lor 03 Tegal Regency. Departing from this problem, researchers conducted a type of development research, or Research and Development (R&D), which focused on products in the form of learning media. The learning media product developed in this study was educational pocket comic media (komikusi). The development model used in this study is the ADDIE development model, which includes five stages: analysis, design, development, implementation, and evaluation. This research aims to determine the feasibility and effectiveness of the media products developed to improve the reading comprehension skills of class IV B students at SDN Harjosari Lor 03, Tegal Regency. Based on the research that has been conducted, the results obtained are that learning media have an important role in the success of learning implementation. The learning media developed by a researcher named Komikusi received a very feasible and effective predicate for use in learning. This is proven by obtaining a feasibility value of 90.9% from media experts and 85.9% from material experts, and the increase in pretest and posttest results, as shown by the recapitulation of T-test and N-Gain test results, with a moderate increase category obtained by class IV B students.